KONSEP GURU DAN PENDIDIKAN AKHLAK MENURUT IMAM AL-GHAZALI - Nukman, Nukman; Munandar, Didih Syakir; Darisman, Dede (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2015)
This research was conducted to analyze the concept of teachers and moral education according to Al-Ghazali contained in Ihya Ulumuddin. The results of the study can be summarized as follows: 1) The concept of teachers and moral education according to Imam Al-Ghazali in the translation of the Book of Ihya Ulumuddin that teachers or educators are people who try to guide, improve, perfect and purify the heart so that it becomes close to the Khaliq. He also gave great attention to the task and position of an educator. This is reflected in his writing: